Analysis of the Effect of Injection Molding Temperature Variations on the Tensile Strength Characteristics of PLA–Cassava Peel Starch Composite Material - Moch. Ally Rochman; Andita Nataria (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Polylactic Acid (PLA) is a type of bioplastic derived from renewable materials such as corn starch and cassava. This material has advantages because it is biodegradable and environmentally friendly. However, PLA has weaknesses in terms of mechanical strength, particularly in tensile strength and resistance to high temperatures. To improve these characteristics, material modification is required by adding natural reinforcing materials. In this study, cassava peel waste was used as a reinforcing material because it contains a high amount of cellulose fiber and is abundantly available. The material fabrication process was carried out using the injection molding method with temperature variations of 160°C, 175°C, and 190°C. Mechanical property testing was conducted using the ASTM D638 standard to determine the effect of temperature on the tensile strength of the PLA + cassava peel composite material. The results showed that variations in processing temperature influenced the tensile strength, where certain temperature increases were able to enhance the flexibility and tensile strength of the material. This research contributes to the development of stronger and more environmentally friendly PLA-based bioplastics. The utilization of cassava peel waste not only improves the mechanical properties of the material but also provides a solution for agricultural waste management. It is expected that the results of this research can be used as a reference for innovations in sustainable alternative materials for various industrial applications.